THE EFFECT OF USING PHET SIMULATIONS ON STUDENTS’ MATHEMATICAL UNDERSTANDING OF FRACTIONS IN FOURTH GRADE ELEMENTARY SCHOOL - Safira Zahra; Kowiyah (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Mastering foundational concepts in primary mathematics is crucial, yet the inherent abstraction of fractions frequently creates substantial learning barriers for young pupils. This investigation evaluated the empirical impact of integrating PhET Interactive Simulations on fourth-graders' comprehension of fraction topics. Using a quantitative single-group pretest-posttest design, the study involved 28 fourth-grade students at SDN Pekayon 03 Pagi as the total sample. Data were gathered through a validated 10-item written instrument measuring core mathematical understanding indicators and analyzed via descriptive and inferential statistics—specifically the paired-samples t-test, normalized gain (N-Gain), and Cohen's d effect size. Findings showed an increase in mean comprehension performance from 64.07 to 87.32. Hypothesis testing confirmed a statistically significant difference (t = -16.262, p = 0.000 < 0.05). Additionally, the average N-Gain reached 0.67 (66.7%), reflecting moderate effectiveness, while the effect size was 3.07, indicating a large effect category. In conclusion, embedding PhET Simulations into instruction aids in visualizing abstract fraction concepts and improving students' mathematical comprehension in elementary education